O DESEJO, O PODER, A SEDUÇÃO: A INTRODUÇÃO DA FUMICULTURA NOS FAXINAIS DE RIO AZUL, REBOUÇAS E IMBITUVA - 1950-1970 - CARVALHO, ROSENALDO DE (2015)
This research was to thread in order to realize the changes that have occurred in Faxinais with the introduction of tobacco growing in their territories. For a better understanding of the work was divided into three main parts. In the first part we present a theoretical and methodological debate on the historiographical do with some discussions considered important to carry out the work. We bring a discussion of the narrative as a way of writing history, permeated by discussions that have outlines the acceptance of the narrative genre as written history. The discussion on the use of memory as the source for the writing of history and the discourse that is between them, how to overcome the old secondary role condition memory before history. In the second chapter the objective was the way of life organization faxinalense, the beginning of the century to the time when the tobacco culture is presented to faxinais as an enticing alternative income, and the third time as it was deployed and accepted, the trade boards and a quick discussion about what was and how came to Brazil and faxinais also discusses how producers were brokered, what the reasons the faxinalenses to opt for new culture, what changes in the cultural system of entailed faxinalenses by a new crop that interfered with centuries-old traditional customs and They were slowly turning and taking a new shape. Contours that were gradually precipitating the end of what is called faxinal system, so that accelerated with the arrival of the "gauchos"